Pengaruh ESG disclosure dan board gender diversity terhadap kinerja keuangan dengan board independence sebagai variabel moderasi - Kandera Rineko Nindya (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of ESG disclosure and Board Gender Diversity on company financial performance, with board independence as a moderating variable. The research population includes energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period, with samples selected using purposive sampling. Data analysis methods include descriptive statistics, classical assumption testing, multiple linear regression, and Partial Least Squares (PLS). The results conclude that: (1) ESG disclosure has no significant effect on financial performance, likely due to its implementation being merely formalistic and involving high costs; (2) Board Gender Diversity has a positive and significant effect on financial performance; (3) Board independence does not significantly moderate the relationship between ESG and performance; (4) Board independence actually weakens the positive effect of gender diversity on performance. These findings emphasize the need for a more substantive ESG approach and a balance between independence and inclusivity in corporate governance. Public interest statements This research serves public interest by promoting transparent, inclusive, and sustainable corporate governance. By examining the impact of ESG disclosure and Board Gender Diversity, this study provides essential contributions for stakeholders, including investors, regulators, and the general public. The findings are expected to encourage fairer and more long-term-oriented governance practices in Indonesian business.